Impact study of hygiene and health counselling as a controlling measure of iron deficiency Anemia - Jayanta Saha; Sahana Mazumder (Sen); Amalendu Samanta (International Journal of Medical Research and Review, 2018)
Background and Aim: Anemia is a moderate to severe public health problem in India. Coverage of anemia programmes are inadequate, safe water and sanitation status is moderate or poor, open defecation rates are significant, incidence of diarrhoeal diseases are high as a results of infection. Though poor bio-availability of iron is the root cause of iron deficiency anemia (IDA) the role parasites infection such as hookworm infection also plays a major role in IDA. There is a link between poor hygiene practices –worm infection –IDA. Hence this study was undertaken to educate women of reproductive age group (WRA) about impact of IDA and how good hygiene practice can eliminate the problem to at least some extent.Methods and Material: Women of reproductive age group(WRA) in rural population were taken randomly for this study. They was first screened for anemia and then IDA. The ID anemic women were then randomly allocated into two groups one as experimental and another as control. Base line hematological parameters and hygiene practices were obtained from them. Only the experimental group was counselled about good hygiene practices. The final hematological parameters and hygiene practices were obtained after eighteen months and were compared for statistical significance.Results: At the end of the study 306 women were found to be non anaemic in experimental group while in control group it was only 78 women. Statistical significant results were obtained in hygiene practices between experimental and control group.Conclusion: Our study hence shows that good hygiene practice does play an important role in controlling anemia.